Innovative production of structural light-weight concrete by manufactured porous basalt aggregates. Issue 1 (1st January 2020) - El-Kafrawy, Haytham Amr; Taher, Salah El-Din; Mahfouz, Sameh Yousef
ABSTRACT: Structural Lightweight Concrete (SLWC) is rarely used in Egyptian construction industry because of the unavailability of appropriate lightweight aggregates that capture its salient features. The aim of this research is to produce aggregates of low density and reasonable strength suitable for SLWC and to add new perspective for the structural lightweight concrete in the Egyptian market causing a reflection on the ECP 203 by adding limitations concerning the lightweight aggregates, as the only limitation for lightweight concrete is to install it for architecture uses. In this paper, an innovative procedure for producing SLWC using locally Manufactured Porous Basalt Aggregates (MPBA) is presented as a side product to basalt fiber industry. The scope of work is an experimental investigation to produce the MPBA then examine the feasibility to obtain SLWC. The physical and mechanical properties of Parent Basalt Rocks (PBR) are calibrated then the methodology of producing MPBA is explained and the obtained properties are assessed. The new MPBA is produced when solid basalt is melted and mixed with polypropylene through an established optimum mixing. The newly proposed process includes a sequence of temperature variations using both methods the Rheocasting and Thixocasting process. The phase diagram is illustrated showing the melting point of the basalt rocks and the MPBA. The produced MPBA is further used for SLWC mixes and the presented data provide the possible properties needed to figure out a new material.